Studi Perbandingan Sifat Mekanik Mortar PPC dan Mortar Geopolimer dengan Aktivator NaOH pada Rendaman Air Laut - Priastiwi, Yulita Arni; Hidayat, Arif; Husna, Khotimatul; Putriagsari, Farah Naurah (MEDIA KOMUNIKASI TEKNIK SIPIL, 2023)
Using Portland pozzolan cement (PPC) is considered suitable for infrastructure in the sea area because it has a high resistance to salt and sulfate but still produces carbon dioxide gas emissions that can damage the environment. Environmentally friendly materials that can completely replace cement are geopolymer materials. This study compared the mechanical properties of PPC mortar and geopolymer mortar with and without white soil under seawater bath conditions. The test object is a 5x5x5 cm mortar cube with fly ash, white soil, sand, water, alkaline activator NaOH 8M, and PPC cement. Mortar variations include PPC mortar, geopolymer mortar without white soil substitution (TTP), and 15% white soil substitution mortar (TP15%). Tests include compressive strength, tensile strength, porosity, density, and absorption for all three variations. Microstructure testing of the influence of the bath is carried out on the TP15% mortar. The test results showed that PPC mortar has better resistance compared to both variations of geopolymer mortar in terms of its compressive and tensile strength at a bath life of 28 days, namely 32,427 MPa and 2,318 MPa, while the geopolymer mortar produced maximum compressive and tensile strength values of 14,373 MPa and 0.993 MPa. TTP mortar has better resistance than TP15% mortar. Microstructure testing showed mortar with baths had a denser matrix.